2019
DOI: 10.1371/journal.pcbi.1006768
|View full text |Cite
|
Sign up to set email alerts
|

Structure, stability and specificity of the binding of ssDNA and ssRNA with proteins

Abstract: Recognition of single-stranded DNA (ssDNA) or single-stranded RNA (ssRNA) is important for many fundamental cellular functions. A variety of single-stranded DNA-binding proteins (ssDBPs) and single-stranded RNA-binding proteins (ssRBPs) have evolved that bind ssDNA and ssRNA, respectively, with varying degree of affinities and specificities to form complexes. Structural studies of these complexes provide key insights into their recognition mechanism. However, computational modeling of the specific recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 92 publications
2
46
0
Order By: Relevance
“…Our comparative analyses show that the SP group proteins form more contacts with DNA bases than those in the NS group (Figure 6 ), and the propensities of amino acids that involved in protein–ssDNA contacts show that both groups prefer aromatic residues and positively charged residues, but residues H, Y and R are more enriched in the SP group (Figure 2 ). These findings are consistent with previous studies ( 50 , 84 , 85 ). The enrichment of all aromatic residues can be attributed to the increased accessibility of ssDNA.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our comparative analyses show that the SP group proteins form more contacts with DNA bases than those in the NS group (Figure 6 ), and the propensities of amino acids that involved in protein–ssDNA contacts show that both groups prefer aromatic residues and positively charged residues, but residues H, Y and R are more enriched in the SP group (Figure 2 ). These findings are consistent with previous studies ( 50 , 84 , 85 ). The enrichment of all aromatic residues can be attributed to the increased accessibility of ssDNA.…”
Section: Discussionsupporting
confidence: 94%
“…An analysis of crystal structures of 10 different non-cognate ssDNA ligands complexed with the Oxytricha nova telomere end-binding protein ( On TEBP) revealed that the overall protein conformation in all complexes remained nearly identical to that of the cognate complex, but the ssDNA exhibited subtle to dramatic conformational changes ( 49 ). Pal and Levy also found that the ssDNA molecules were more flexible than the proteins, but they suggested that the sequence specificity was mostly introduced by the stacking interactions between aromatic residues and DNA bases ( 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA is well known as the repository of genetic information shared by all forms of eukaryote life. Compare the fragility of single-stranded DNA (ssDNA) with the unparalleled stability of double-stranded DNA (dsDNA) 67 , 68 . The paired strands of dsDNA, bound together, are relatively resistant to random damage because each strand is in constant interaction with its sister strand; the two strands can be perceived to be in continuous cooperation; essentially all potentially reactive, non-covalent bonding energy is engaged in cooperative interactions between the strands.…”
Section: Interactionsmentioning
confidence: 99%
“…Single-stranded RNA (ssRNA) is also known to serve as an agonist of TLR-7/8 and retinoic acid-inducible gene I (RIG-I), which can induce innate immune responses and increase immunogenicity [26,27]. Compared to dsRNA, ssRNA can induce appropriate immune responses and does not remain in the body for a long time [28,29], resulting in fewer intense adverse effects. Currently, ssRNA is being studied as an intrinsic adjuvant in tumor-vaccination studies [30,31,32].…”
Section: Introductionmentioning
confidence: 99%